Method for calculating the intersection points of meteor stream orbits with a plane - Борбулев, Станислав Игоревич; Волощук, Юрий Иванович; Черкас, Юрий Васильевич (Eastern-European Journal of Enterprise Technologies, 2013)
Current functions of orbit elements distance in space (Dsh− Sutvort’s and Hawkins’s criterion, Dr−Drumond’s criterion, etc.), despite the same goal, can give significantly different distance parameters for one and the same range of input parameters, and even for one of the same pair of orbits. In general, each of the existing D-criteria is acceptable for determining the distance between orbits only in certain areas of possible orbits. The research describes a method and algorithm for calculating the intersection points of meteor orbits with a plane, perpendicular to the mean orbit of meteor stream at a given angle of true anomaly. The position of these intersections in characteristic points of the mean orbit allows investigating the fine structure of a meteor stream and checking the stream allocation quality using the D-criteria. This method will help to resolve controversial situations, when different D-criteria provide substantially different distance parameters for the same orbits.